2021
DOI: 10.1051/e3sconf/202125803008
|View full text |Cite
|
Sign up to set email alerts
|

Successional structure and useful condition of mowing-and-grazing landscapes

Abstract: The paper presents data on the indicators of livestock production, the number of farm animals and poultry in the Tyumen region. The characteristics and significance of near-village forage lands are given. The studied forage lands are assigned to the forest-steppe lowland latitudinal-zonal area of the Kurgan province and contain valuable species of herbs: Calamagrostis epigejos, Bromopsis inermis, Festuca pratensis, Vicia villosa Roth, Trifolium rubens L., Medicago falcata. The territory of pastures is used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The inventory and analytical stage of collecting materials showed that the tract of the agrolandscape has a northern exposure of the slope, the slope is directed to the floodplain of the Emurtla River [10], the height above sea level varies from 82 meters to 75, as a result, the facies of the tract are dissected by erosion processes. The proximity of arable land to the swampy floodplain of the river causes the transition of soils from the automorphic series to the alluvial one.…”
Section: Resultsmentioning
confidence: 99%
“…The inventory and analytical stage of collecting materials showed that the tract of the agrolandscape has a northern exposure of the slope, the slope is directed to the floodplain of the Emurtla River [10], the height above sea level varies from 82 meters to 75, as a result, the facies of the tract are dissected by erosion processes. The proximity of arable land to the swampy floodplain of the river causes the transition of soils from the automorphic series to the alluvial one.…”
Section: Resultsmentioning
confidence: 99%
“…In the interstitial falls there are peat soils -boggy, grassy, peaty and meadow soils. All soils are of heavy and clayey texture [2,5,9,12].…”
Section: Methodsmentioning
confidence: 99%
“…Agriculture as an economic activity is based on meeting the needs of the population for fresh and nutritious food, but is also one of the sources of pollution of the components of the environment [1][2][3][4][5][6][7]. At present, the negative impact of agricultural production on the environment, one of which is untreated wastewater [8][9][10][11][12][13][14][15][16][17], is advancing. Wastewater carries dangerous chemical compounds, pathogenic microorganisms, biogens included in fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…For the successful development of agroecological aspects of weed control, it is necessary to know the relationship between cultivated and weeds, learn how to manage them. However, it must be remembered that weeds have a higher ecological plasticity compared to cultivated plants [11].…”
Section: Introductionmentioning
confidence: 99%